Moderasi beragama dalam perspektif Al-Qur’an dan Al-Hadits - Maulani, Kharisma (Maliki Interdisciplinary Journal, 2024)
The population of Indonesia has ethnic, religious, linguistic, social and cultural status diversity. Diversity can be a force of integration that establishes society, but it can also be a cause of conflict between races, tribes, cultures, religions and between norms of life. Therefore, the understanding of religious moderation needs to be planted not textually, but contextually. The purpose of this study is to provide an overview of religious moderation in terms of meaning, history of emergence, indicators, and perspectives of the Qur'an and hadith on this matter. The research method used is qualitative research with a literature study approach. The result of this study is that religious moderation refers to how we practice our religion in the context of other communities, especially those of different religions, in a straightforward and not extreme, radical, or hateful manner, which can cause rifts and divisions in interreligious relations. The idea of religious moderation first emerged as a result of intolerant behavior in religion, where some people use their religion as a justification for committing acts of violence against religion and other groups. Islamic moderation has the goal of Rahmatan lil 'Alamin. There are several indicators of religious moderation, namely: national commitment, tolerance, non-violence, and accommodating to local culture. In Islam, both in the Qur'an and hadith, it strongly supports religious moderation. In Islam itself, religious moderation has the concept of "ummatan wasathan" or just and moderate people.